Distribution of Zinc (II) Between Buffered Aqueous Phases and Organic Phase of 4,4´-(1E,1E´)-1,1´-(Ethane-1,2-Diylbis (Azan-1-Yl-1ylidene) Bis(5-Methyl-2-Phenyl-2,3-Dihydro-1h-Pyrazol-3-Ol) (H2BuEtP) in Chloroform - Godwin, J.; Benson, Oguarabau; Polokeduo, N. R. (European Journal of Applied Sciences, 2024)
The distribution of Zn(II) between buffered aqueous solutions and chloroform solution of a Schiff base 4,4´-(1E,1E´)-1,1´-(ethane-1,2-diylbis(azan-1-yl-1ylidene))bis(5-methyl-2-phenyl-2,3-dihydro-1H-pyrazol-3-ol) (H2BuEtP) was studied. A range of buffers from pH 2.30 – 8.50 was used and the working concentration of Zn(II) was 50 mgl-1. Equilibration time of 1 hour was used and results were obtained by comparing standard absorbance with raffinates absorbances using AAS at wavelength of 213.9 nm. Plots of log D against pH gave the optimal pH values of 4.8 and 7.5 with percentage extraction of > 90%. pH 5.8 was determined as pH1/2 where 50% extraction of Zn(II) was achieved. Log D against Ligand and Zinc concentrations plots showed a reaction mole ratio of 1:1 between Zn(II) and the ligand (H2BuEtP) with the ligand losing only a proton instead of the expected 2. Calculated log D and log Kex values were -3.05 ± 0.14 and -2.52 ± 0.55 respectively and compared with values for other metals studied with same ligand (H2BuEtP), it indicated that the ligand (H2BuEtP) was a poor extractant for Zn(II) but the formed complex Zn(HBuEtP)X had high stability. The structure of the formed complex Zn(HBuEtP)X was proposed using slope analysis and a tetrahedral structure with Zn(II) sp3 hybridized was also proposed.